Вибір доцільних режимів роботи холодильної установки методом ексергетичного аналізу - Лабай, В. Й.; Ярослав, В. Ю. (Видавництво Державного університету “Львівська політехніка”, 1999)
The exergetic analysis of the one-step freon cooling plant with the regenerative heat exchanger for all temperature regimes wich are typical for air conditioning systems is considered in this paper (1). It was defined the optimum temperature 3 regime.
Keywords: 621.59.01 (075.8)